Evaluation of Nurses’ Performance Regarding Personal Protective Equipment at Rania Teaching Hospital - Omar Sharif, Bayan; M. Khdir, Frishta; M. Khdir, Padasht; A. Rasul, Sarezh (Kurdistan Journal of Applied Research, 2019)
Personal protective equipment (PPE) refers to protective clothing that acts as a barrier between infectious materials such as viral, bacterial contaminants and the skin, mouth, nose, eyes and mucous membranes. It includes gloves, mask, eye goggles and gown. It is a shortage of study of university students. The aim of the current study was performing to provide demographic data and to evaluate nurse’s performance regarding PPE at Rania teaching Hospital in Kurdistan region of Iraq, during the period of 10th October up to 7th of March. A non- probability purposive sample of (72 nurses), data collection of the study instrument was constructed of total (42) items. A professional team that contains of (11) experts were performed validity of the instrument. Reliability of the instrument was determined through the use of Equivalence (inter-rator or inter-observer), the data were collected through the use of evaluation technique then organized and coded into computer files. Statistical approaches were uses for data analyzed, also data analysis by (SPSS version 25). The result has revealed that highest age of the sample was between 30-39 years and most of them were institute nurses and more than half of nurses had less than 10 years of employment but most of them not trained yet. The majority of nurses were performed many nursing procedures such as wound dressing, suturing, suctioning, naso-gastric tube and Foley catheter insertion without using PPE properly and without washing hands before procedures. Also, there was no significant relationship between personal protective equipment and some socio- demographic data. The researchers recommended training course regarding personal protective equipment by the ministry of health/infection control department and participants of symposia.